Construction of a new chiral hetermetallic Gd(III)–Cu(II)–camphorate: photocatalytic property and application values in the treatment of pancreatitis. Issue 9 (1st August 2022) - Ye, Li-Na; Yu, Shan; Gao, Tian-Yi; Ren, Yu-Han
Abstract: Employing the dicarboxylate ligand of D-H2 cam to react with Gd2 O3 and Cu(NO3 )2 ·3H2 O under hydrothermal conditions, we successfully prepared a new heterometallic compound, namely [Gd2 Cu(D-cam)4 (H2 O)]n (1, D-H2 cam is d -(+)-camphoric acid). Moreover, the photocatalytic performance was also explored for the methylene blue (MB) solution degradation under the irradiation of ultraviolet light. Its application values on the pancreatitis treatment were examined and the corresponding mechanism was tested in meantime. Firstly, the cell counting kit-8 (CCK-8) assay was conducted and the compound's inhibitory effect against the pancreatitis cells viability was detected. Besides, the detection of the inflammatory cytokines content released into plasma was performed enzyme-linked immunosorbent assay (ELISA) detection.